Pengaruh Opini Big Firm, Penerapan Corporate Governance dan Ukuran Perusahaan Terhadap Kualitas Laporan Keuangan Pada Perusahaan Non-Cyclical Yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024 - Intan Farica; Rina Hartanti (AKUNTANSI 45, 2026)
Financial statement quality is an essential aspect of enhancing transparency, accountability, and stakeholders' confidence in corporate financial information. The quality of financial statements is influenced by various factors, including Big Firm audit opinions, the implementation of corporate governance, and firm characteristics.This study aims to examine the effect of Big Firm audit opinions and corporate governance implementation on financial statement quality, with firm size serving as a moderating variable in non-cyclical companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This research employed a quantitative approach with a causal research design. The study utilized secondary data obtained from the companies' annual reports. The sample was selected using a purposive sampling technique, while data analysis was conducted using multiple linear regression and Moderated Regression Analysis (MRA) with IBM SPSS version 26. The findings indicate that Big Firm audit opinions have a positive and significant effect on financial statement quality. Corporate governance, proxied by the proportion of independent commissioners, has a negative and significant effect on financial statement quality.